Fiqh Teacher's Strategy in Improving Understanding of the Book of Fathul Qarib at the Talaqqi Centre Indonesia Al-Qur'an House - Zulpirandi Nainggolan; Muhammad Ruslan (MASI Mandiri Edukasi, 2026)
This article analyzes the strategies of Islamic jurisprudence teachers in improving the understanding of the Fathul Qarib book at the Talaqqi Center Indonesia House of the Qur'an. This research uses a case study method with a qualitative approach. The results show that learning through the syawir (deliberation) strategy with the division of roles of reader, muradi (translator), and mubayyin (explainer) is able to improve students' ability to understand Islamic jurisprudence material independently. The novelty of this research lies in the application of syawir based on the active role of students in learning classical Islamic jurisprudence books that strengthen understanding, critical thinking, and communicative skills. The learning obstacles include differences in student abilities, lack of concentration, suboptimal implementation of syawir, differences in academic ability, and learning environment factors. Meanwhile, supporting factors include teacher guidance and motivation, the availability of supporting books, and evaluative academic activities. This study recommends the development of syawir strategies through effective time management and intensive teacher mentoring, as well as its application in the learning of other Islamic jurisprudence books in similar institutions.